Non‐isolated high step‐up DC–DC converter based on switched‐inductor switched‐capacitor network for photovoltaic application - Hossein Jalali Farahani; Mahdi Rezvanyvardom; Amin Mirzaei (IET Generation, Transmission & Distribution, 2023)
Abstract A high step‐up non‐isolated DC–DC converter based on a switched‐inductor/switched‐capacitor network is proposed in this paper. The proposed converter takes advantage of both active and passive switched inductor cells. Inductors L1 and L2 can be connected in series to increase the voltage gain. Furthermore, the conduction losses of the proposed converter are low which leads to an increase in its efficiency. The proposed converter takes advantage of the voltage multiplier at the output. As a result, the voltage across all output capacitors is half the output voltage. Moreover, the switched capacitor network in the proposed converter can be extended to achieve higher voltage gain. The comparison is done with other similar topologies in detail to prove the effectiveness of the proposed converter. Operation modes, design procedures, and the control scheme are analyzed. A 200‐W DC–DC converter is implemented and tested. The experimental results confirm the theoretical analysis and its successful operation. The maximum efficiency is above 94%.